P14.01.B Isolation and characterization of circulating tumor cells in a glioblastoma case with recurrence at distance and correlation with tumor mutational status. (5th September 2022) - Lessi, F; Morelli, M; Aretini, P; Menicagli, M; Franceschi, S; Pasqualetti, F; Gambacciani, C; Di Stefano, A; Santonocito, O; Mazzanti, C M
Abstract: Background: Circulating Tumor Cells (CTCs) are considered to be one of the important causes of tumor recurrence and distant metastasis. For many years, glioblastoma (GB) was thought to be restricted to the brain. Nevertheless, a growing body of evidence indicates that, like many other cancers, hematogenic dissemination is a reality. The absence of a procedural uniformity in literature prompted us to develop an innovative and sensitive method to obtain CTCs in GB. Our aim is to define the genetic background of single CTCs compared with the primary GB tumor and its recurrence to assess whether or not their presence in the peripheral circulation correlates with GB migration and dissemination. Material and Methods: CTCs were enriched from whole blood of one patient with recurrent GB with Parsortix Cell Separation System and analysed on DEPArray system. After that, CTCs Copy Number Aberrations (CNAs) and sequencing analysis was performed to compare CTCs genetic background with the same patient's primary and recurrence tissues, analysed by NextSeq 500 (whole exome sequencing). Results: We obtained 211 mutations in common between primary and recurrence tumor. Among these, three somatic mutations (c.430 G>A in PRKCB gene, c.815 C>T in TBX1 gene and c.1554 T>G in COG5 gene) were selected to investigate their presence in recurrence CTCs. Almost all of the sorted CTCs (9/13) had at least one of the mutations tested. Conclusion: In confirmation of the hypothesis, the CTCs detected in the patient's blood were actually cancer cells deriving from GB tumor.